TEACHERS’ PERCEPTION ON CLASSROOM ACTION RESEARCH IN ENGLISH EDUCATION AMONG ENGLISH TEACHERS IN CIAMIS WEST JAVA - Rina Herlina; Asep Dudi Kurnia; Didih Faridah (JALL (Journal of Applied Linguistics and Literacy), 2018)
This study is a survey- based research about teachers’ perception on classroom action research in English education among English teachers  in  Ciamis.  The objective of  the study  is to investigate how English teachers perceive on classroom action research in teaching English. It varies among English teachers, indeed. Thus, this survey reveals their sight, point of view, and expectation toward classroom action research. Open-ended questionnaire is the only instrument given to 20 respondents during the survey. It consists of 4 questions. Simple random sampling has been applied. All of them are English teachers from elementary schools, junior high schools, senior high schools and vocational schools in Ciamis. Ten of them are civil servants and the other ten are not. They are from certified and non certified teachers. The survey result shows different English teachers’ perception on classroom action research in percentage display taken from four questions.  Almost all respondents know the function of classroom action research in connection with finding the solution of overcoming some students’ learning problems in the classroom. Some of them have ever made classroom action research and know its procedure. All of them expect the government not to put pressure on English teachers to make classroom action research as the requirement unless they will get sanction due to the fact that it is instructed by the Education and Culture ministry. The conclusion is classroom action research has been a big concern among English teachers in Ciamis. The suggestion then goes to all English teachers to conduct classroom action research as an action to develop their teaching quality not to gain the government reward. Keywords: classroom action research, English teachers, teachers’ perception